A Comparison of Repetitive Negative Thinking and Post-Event Processing in the Prediction of Maladaptive Social-Evaluative Beliefs: A Short-Term Prospective Study - Wong, Q.; McEvoy, Peter; Rapee, R. (Springer New York LLC, 2015)
© 2015 Springer Science+Business Media New York. Theoretical models propose that transdiagnostic and disorder-specific repetitive thinking processes each interact with individual environmental conditions to predict symptoms. The current study aimed to test this hypothesis in the context of social anxiety. Specifically, we aimed to predict future maladaptive social-evaluative beliefs (high standard, conditional, and unconditional beliefs) from: (a) the transdiagnostic tendency to engage in repetitive negative thinking (RNT), (b) the social anxiety-specific tendency to engage in post-event processing (PEP), and (c) the interaction of these repetitive thinking tendencies with the frequency of recent negative social events and social anxiety levels. An initial undergraduate sample (N = 331) was recruited and 215 participants completed measures of the constructs of interest at two time points within an acceptable timeframe (average 8.44 days apart). Using hierarchical linear modelling, significant interactions were only obtained for conditional and unconditional beliefs with a specific component of PEP that focuses on thinking about the past involved in prediction. Follow-up simple slopes analyses indicated mainly no change in these beliefs or decreasing trajectories over time for different combinations of levels on the predictor variables. However, for participants with high social anxiety levels who experienced a high number of recent negative social events, those who reported low levels of thinking about the past exhibited a pattern of increasing trajectories for conditional and unconditional beliefs. These findings indicate that RNT and PEP differ in their ability to predict social-evaluative beliefs, and highlight the importance of research comparing different types of repetitive thinking to better understand these processes.